Entangled: Three Arctic Communities, Textiles, and Mid-Century Modernisms in Canada - Burgess, Jennifer (2023)
The emergence of modern Inuit women’s textiles began in the 1950s through efforts of southern Canadian instructors and government-backed intermediaries. Inuit textile works became enmeshed in intersections of discourse, institutions, and power which assigned cultural value to artistic commodities. These histories were concurrent with the development of Canadian modernities. This dissertation examines the relationship between mid-twentieth-century discourses of Western aesthetic modernism, its related institutional practices, and the development of a textile market in the Arctic between 1950 and 1980. It explores how textile artists navigated these art worlds to generate economic opportunities in northern communities. This document also examines consumer tastes during this period as art markets became more frantic, competitive, and troubled by concerns about authenticity, reproduction, and purchasing ethics. To address these histories, this document investigates the systems that governed Inuit textiles, their development, and how Inuit textile makers navigated those systems. To answer these questions, it considers three Arctic textile production communities: Kinngait printed fabrics, Qamani’tuaq embroidered wall-hangings, and Pangnirtung tapestries. The resulting argument posits that modernity in Canada is not a monolithic period, and that by tracing the pathways taken by artists in these three Northern communities, and by members of the southern Canadian art world, this project indicates the fluctuating nature of Canada’s modernities – plural. This project uncovers those objects that exist beneath the surface of histories and scholarship which leave out the Inuit women’s experiences. It pulls back the smooth cover of modernity and reconnects the disparate forms of mid-century North American textiles. In doing so, it demonstrated the resilience of Inuit women in unpredictable economic environments. This document also illuminates the taste culture, nostalgia, and struggles for identity that defined Canada in the ...